Rational selection of superparamagnetic iron oxide/silica nanoparticles to create nanocomposite inductors. Issue 38 (16th September 2015) - Rowe, Michael P.; Sullivan, Sean; Desautels, Ryan D.; Skoropata, Elizabeth; van Lierop, Johan
Abstract : The detailed structure/composition of superparamagnetic Fe3 O4 /γ-Fe2 O3 /iron orthosilicate/silica core/inner-shell/middle-shell/outer-shell nanoparticles and their performance as inductor device is reported. Abstract : The detailed characterization of core/shell iron-oxide/silica nanoparticles reveals how these superparamagnetic systems are actually composed of a Fe3 O4 inner core, γ-Fe2 O3, outer core, iron orthosilicate interphase layer, and exterior silica shell. The performance of a superparamagnetic inductor device is then reported for the nanocomposite formed from the binder-free consolidation of these core/shell nanoparticles.